STUDI RESPON DAERAH ALIRAN SUNGAI CIMANYAR TERHADAP BERBAGAI KEJADIAN HUJAN - Fuad Hasan; Bambang Eko Widyanto; Raden Herdian Bayu Ash Siddiq (Jurnal Ilmiah Teknologi Infomasi Terapan, 2019)
The Cimanyar River Basin is one of the Cimanuk watersheds. There is a rain and debit recording station with the duration of hours. Based on the data obtained in the field there is a significant difference in the watershed response. The hydrograph of the rainfall event on February 4, 2013 shows the surface runoff in the watershed. While the hydrograph of rainfall events on 27 October 2012 indicates the existence of a subsurface flow mechanism (interflow). To see the watershed response, this study developed a hydrological model with MIKE SHE which was calibrated and validated with measurement discharges at the Cimanyar observation station.